2018
DOI: 10.1097/md.0000000000011239
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal default-mode network homogeneity in patients with temporal lobe epilepsy

Abstract: Default-mode network (DMN) plays a key role in a broad-scale cognitive problem, which occurs in temporal lobe epilepsy (TLE). However, little is known about the alterations of the network homogeneity (NH) of DMN in TLE. In the present study, we employed NH method to investigate the NH of DMN in TLE at rest.A total of 47 patients with TLE (right TLE [rTLE] 29, and left TLE [lTLE] 18) and 35 healthy controls who underwent resting-state functional magnetic resonance imaging were enrolled. NH approach was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…These brain networks can be derived from resting state functional magnetic resonance imaging (rsfMRI), and are supporting a variety of sensory, cognitive and behavioural functions [7,8]. Perturbed functionality of RSNs contributes to a range of brain diseases including epilepsy [9], Alzheimer's disease [10], autism [11], depression [12] and schizophrenia [13]. Although alterations of RSNs have been subject to numerous studies, characterization of their complex dynamics remains an open question in the brain sciences [1,[14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These brain networks can be derived from resting state functional magnetic resonance imaging (rsfMRI), and are supporting a variety of sensory, cognitive and behavioural functions [7,8]. Perturbed functionality of RSNs contributes to a range of brain diseases including epilepsy [9], Alzheimer's disease [10], autism [11], depression [12] and schizophrenia [13]. Although alterations of RSNs have been subject to numerous studies, characterization of their complex dynamics remains an open question in the brain sciences [1,[14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…All the participants were instructed to lie still and stay awake with their eyes closed. The scanning parameters were as follows: repetition time/echo time (TR/TE) 2,000/30 ms; 31 slices; 90° flip angle; 220 × 220 mm field of view; 5 mm slice thickness; and 1 mm pitch [the detailed steps were excerpted from our previous study ( 32 ), and detailed information can be found in the Supplementary Material ].…”
Section: Methodsmentioning
confidence: 99%
“…Several spurious covariates were removed, such as the signal from a region centered in the white matter and the signal from a ventricular seed-based region of interest, as well as the six head-motion parameters obtained by rigid body correction. The global signal was retained during the processing of the resting-state functional connectivity data [the detailed steps were excerpted from our previous study ( 32 ), and detailed information can be found in the Supplementary Material ].…”
Section: Methodsmentioning
confidence: 99%
“…TLE is increasingly thought to be a disorder involving abnormal epileptogenic networks, rather than a single focal epileptogenic source ( 16 – 18 ). Accumulating evidence has shown that TLE exists in several networks disturbances, including alertness network ( 19 ), attention network ( 20 ) and default mode network (DMN) ( 13 , 21 , 22 ). However, there are only a few reports concerning the DMN and its function in patients with TLE.…”
Section: Introductionmentioning
confidence: 99%